2013
DOI: 10.1111/febs.12519
|View full text |Cite
|
Sign up to set email alerts
|

A S52P mutation in the ‘α‐crystallin domain’ of Mycobacterium leprae HSP18 reduces its oligomeric size and chaperone function

Abstract: Mycobacterium leprae HSP18 is a small heat shock protein (sHSP). It is a major immunodominant antigen of M. leprae pathogen. Previously, we have reported the existence of two M. leprae HSP18 variants in various leprotic patients. One of the variants has serine at position 52, whereas the other one has proline at the same position. We have also reported that HSP18 having proline at position 52 ( HSP18P 52 ) is a nonameric protein and exhibits chaperone function. However, the structural and functional characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(88 citation statements)
references
References 68 publications
6
82
0
Order By: Relevance
“…To confirm whether changes in the DTNB assay were due to the alteration in the available free thiol moieties of cysteine residues, we performed the assay using the cysteine-lacking Mycobacterium leprae HSP18, which we have previously cloned and purified. 24 We did not observe a change in the absorbance value at 412 nm with time for HSP18. Collectively, these results confirmed that acetylation of γD-crystallin altered the microenvironment of cysteine residues in a manner that rendered them inaccessible for reaction with DTNB.…”
Section: Resultsmentioning
confidence: 57%
“…To confirm whether changes in the DTNB assay were due to the alteration in the available free thiol moieties of cysteine residues, we performed the assay using the cysteine-lacking Mycobacterium leprae HSP18, which we have previously cloned and purified. 24 We did not observe a change in the absorbance value at 412 nm with time for HSP18. Collectively, these results confirmed that acetylation of γD-crystallin altered the microenvironment of cysteine residues in a manner that rendered them inaccessible for reaction with DTNB.…”
Section: Resultsmentioning
confidence: 57%
“…We also demonstrated that thermally stressed MDH and ADH retained their enzymatic activity to a larger extent in the presence of C-terminal-truncated mutants (except Hsp16.3DC1 and Hsp16.3DC2) than wild-type Hsp16.3. The surface hydrophobicity of Hsp16.3 as well as other sHsps is mostly probed by bis-ANS, a hydrophobic fluorophore [1,9,33,[45][46][47]. Among these, surface hydrophobicity is believed to be one of the important factors behind the modulation of the chaperone function of different sHsps under various conditions [9,33,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…The reported spectra were the average of five scans [45,47]. Spectra were collected from 200 to 260 nm using a rectangular quartz cell with 1 mm path length.…”
Section: Circular Dichroism Measurementsmentioning
confidence: 99%
See 2 more Smart Citations